Top spray fluidized bed granulated paddy urea fertilizer - Subramonian, S. (Trans Tech Publications Ltd, 2014)
Top spray granulation process is a common technique used widely in pharmaceutical, food and special chemical modification for fertilizer manufacturing. Nevertheless, there is still a lack of studies regarding to the description of controlled parameters with dynamic correlation in targeting to produce urea granules. Thus, this research was carried out to introduce the crucial applied process parameters using top spray technique for paddy urea fertilizer production. The acquisition process parameter readings were verified by obtained yield of urea granules (UG) which featured as an optimum particle diameter size from 2 mm to 6 mm with reasonable hardness (crush strength) in range 2.0 kg/granule to 4.0 kg/granule, these criteria were required as a slow-release mechanism during soil adsorption interaction in paddy field to reduce amount of fertilizer consumption. Three significant parameters have been selected namely as air inlet temperature, the viscosity of binder solution and rate of top spraying from starch liquid binder to generate greater UG size from wet granulation interaction with smooth coalescence and consolidation growth. The data classification was screened by One-Factor-at-a-Time (OFAT) 101 method and supported by 2 levels and 3 factors (23) of full factorial design for clear description to vindicate the critical parameter required during urea granulation using fluidized bed granulator corresponds to low energy consumption and economical process. The obtained parameter readings and findings of UG features were useful to be applied further for detail investigation on next stage regarding to agglomeration profile and mechanism using CCD camera and PDA monitoring devices. Â© (2014) Trans Tech Publications, Switzerland.